Le château médiéval, forteresse habitée (XIe-XVIe s.) Archéologie et histoire : perspectives de la recherche en Rhône-Alpes - Poisson, Jean-Michel (Documents d'archéologie française, 1992)
Who were the inhabitants of the castle, the main center of power during the Middle-Ages? What um their life style? These are some of the many questions to which this Collective study hopes to reply. Confronted by archaeological and written evidence, unusually treated here as sciences auxiliary to archaeology we are offered here an unusual lieu of a sparsly inhabited castle. This study is centred on the region of the Rhône-Alpes with several incursions for comparison in Alsace, Spain and in Poland, their objective goes far outside the regional limits and should provoke the interest of all archaeologists and medieval historians.